Pondok Pesantren dan Jihad: Studi Tentang Pembelajaran Konsep Jihad di Pondok Pesantren Nurussalam Ciamis - Jalal, Abdul; Aziz, Abdul (Jurnal Penelitian Pendidikan Islam, 2017)
This article discusses the learning model of "jihad" concept in Pondok Pesantren Nurussalam Ciamis. The results showed (1) Pondok Pesantren Nurussalam apply  integrative curriculum between government curriculum and pesantren curriculum; (2) in this pondok pesantren there is no learning of jihad concept in particular, that there is study of Islam religion in which can not be separated from jihad theme; (3) based on the curriculum used and the ongoing learning process, the learning result of the jihad concept makes the students become stronger aqidah, more true in worship, and has high jihad spirit; (4) this boarding school does not inculcate the concept of jihad with a radical understanding.